2003
DOI: 10.1021/ac034789i
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Carbazole Derivative:  High Sensitivity for Quadruplex DNA

Abstract: We have synthesized a novel molecule, 3,6-bis(1-methyl-4-vinylpyridium)carbazole diiodide (BMVC), for recognizing specific quadruplex structures, particularly the quadruplex of human telomeric sequence d(T(2)AG(3))(4). The fluorescence intensity of the BMVC molecule increases from 1 to almost 2 orders of magnitude upon interacting with various DNAs. At a concentration of BMVC of 10 microM, fluorescence bands with different colors of BMVC in electrophoresis gels of various DNAs can be observed. The fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 29 publications
3
83
0
1
Order By: Relevance
“…There is evidence to suggest that G-quadruplexes exist in vivo, and it is believed that these structures act as signaling elements (22)(23)(24); however, direct evidence for the formation of these structures in vivo is still emerging. For example, the identification of antibodies and proteins that preferentially bind to, stabilize, unwind, or cleave G-quadruplexes provides evidence for their existence in vivo (25,26).…”
mentioning
confidence: 99%
“…There is evidence to suggest that G-quadruplexes exist in vivo, and it is believed that these structures act as signaling elements (22)(23)(24); however, direct evidence for the formation of these structures in vivo is still emerging. For example, the identification of antibodies and proteins that preferentially bind to, stabilize, unwind, or cleave G-quadruplexes provides evidence for their existence in vivo (25,26).…”
mentioning
confidence: 99%
“…Recently, we have synthesized a novel carbazole derivative of 3,6-bis[2-(1-methylpyridinium)vinyl]carbazole diiodide (BMVC; Scheme) to stabilize the quadruplex structure of d(T 2 AG 3 ) 4 (Hum) [22] and to illustrate its distinct fluorescence properties [23]. We found that the melting temperature of the quadruplex structure of Hum increases by ca.…”
mentioning
confidence: 99%
“…In comparison, the enhancement of BMVC fluorescence is slightly lower upon interaction with HT24 (quadruplex) than that of LD12 (duplex) in our previous work. 22 Fluorescence titration was carried out to measure the binding affinities of o-BMVC to LD12 and HT24. Figure 3 shows the fluorescence spectra of 10 μm of o-BMVC by adding DNA from 0.25 to 8 μm.…”
Section: Confocal Microscopymentioning
confidence: 99%